Interaksi Bank Syariah dan Variabel Makroekonomi dalam Mendorong Pertumbuhan Ekonomi di Negara Berkembang - Kismawadi, Early Ridho (IAIN Langsa, 2023)
This study aims to examine the empirical impact of the Islamic banking sector, inflation rate, and currency exchange rate on the economic growth of Saudi Arabia, United Arab Emirates, Kuwait, Malaysia, Qatar, Bahrain, and Bangladesh from 2014 to 2022. For the purpose of further investigation, a total of 717 observations were selected according to certain criteria. The sample consisted of 24 banks from seven countries that have the highest aggregate assets on a global scale. Data is collected quarterly. This research approach is quantitative research using the Vector Error Correction Model as an analysis technique. Long-term analysis is tested using cointegration analysis. Impulse response function (IRF) and variance decomposition (VD) techniques were used in this study to show how each macroeconomic variable shock affects the short-term dynamic path of all system variables. The results of the study found that the shock of the majority of research variables was responded positively by GDP except for inflation which in the initial period of the shock was responded negatively by GDP. The results of the Variance Decomposition GDP analysis can be explained that in the initial period GDP variance was formed sequentially from the exchange rate variance, inflation, Total Assets of Islamic Banks, Total Assets of Islamic Banks, and the contribution of Islamic bank assets continued to increase during the observation period.